THE RELATIONSHIP BETWEEN GRAMMAR LEARNING STRATEGY USE AND LANGUAGE ACHIEVEMENT OF IRANIAN HIGH SCHOOL EFL LEARNERS - Sorour Zekrati (Indonesian EFL Journal, 2017)
This paper sought to explore the relationship between grammar learning strategy use and language achievement of Iranian high school EFL learners. The participants of the study were 300 students from three different proficiency levels (Elementary, pre-intermediate, and intermediate), 230 of whom completed and returned an Oxford Solution Test, and a Likert-scale Grammar learning strategies questionnaire (GLSQ) containing 35 statements. The participants were divided to the above mentioned proficiency groups based on Oxford placement test categorization and their total GPAs. The results of descriptive statistics, interview session, and rank-ordering indicated that cognitive and social affective strategies were the most frequently grammar strategies used by Iranian EFL learners. The analysis of the quantitative and qualitative data revealed that Iranian high school EFL learners used a variety of learning strategies while learning and using grammar structures; however, the results of one-way ANOVA indicated that there was a significant difference in the frequency of use of grammar learning strategies among different proficiency levels. Additionally, the results of ANCOVA analysis showed that gender did not play a significant role in strategy use. Furthermore, the results of Pearson correlation coefficient indicated that there was a positive relationship between language achievement and grammar strategy use. The findings of the study might provide Iranian EFL teachers and learners with some helpful implications for teaching and testing, and learning grammar strategies respectively at high schools, as well as useful directions for future studies in this domain.Keywords: grammar learning strategies, language proficiency, language achievement, gender